Da «selvaggi» a «moretti» Schiavitù, riscatti e missioni tra Africa ed Europa (1824-1896) - Ghedini, Giacomo (Premio Istituto Sangalli per la storia religiosa, 2023)
During the 19th Century, more than 2000 children of sub-Saharan origin were redeemed from slavery by missionaries and educated in Europe with the aim of sending them back to Africa as «indigenous missionaries». Yet, so far this phenomenon has found no place in historiography and collective memory. Forgotten, perhaps, or removed. The so-called «moretti» were not mere anonymous satellites, orbiting around the European missionaries. Victims of the choices of others, but also protagonists according their own choices, they were real «agents of history». This book is a first attempt to remove them from the peripheries of our narratives and to return them a place and a name. The archives show it clearly: African-Europeans are far from being just recent actors of European history.